EFFECT OF AGE AND PRESSURE OF THE REAR TIRE OF TRACTORS PERFORMANCE INDICATORS USING THE DISC PLOW - Arkan Muhammad Amin Seedeq; Farooq Dawas Mahmood (Mesopotamia Journal of Agriculture)
The research included a standard study of the age of the which tires are (80%) and (50%) of standard condition and the inflation of the rear tire of the boat are (32) psi and (27) psi and the affect in both of the following properties(draft force, loss power to slippage, fuel consumption, effective field capacity, energy utilization efficiency, volume of soil disturbed, soil penetration resistance, dry bulk density) The experiment was carried out in a global experiment by using the Duncan test with experimental design (RCBD) was used to show the significance of the differences between the average transactions. The result showed a significant effect of the age of the tires in all the studied traits except for the description of the apparent density and showed a significant effect of the pressure factor of the tire bulge in all studied traits except of effective field capacity, volume of soil disturbed, dry bulk density. All the studied traits were significantly affected by the dual interference between the age of tires and pressure of bulge except for the dry bulk density which did not affect significantly.